2013
DOI: 10.4238/2013.february.27.5
|View full text |Cite
|
Sign up to set email alerts
|

More severe clinical course of cardiovascular dysfunction in intensive care unit patients with the 894TT eNOS genotype

Abstract: ABSTRACT. The endothelial nitric oxide synthase (eNOS) plays an important homeostatic role in the cardiovascular system (CVS) by maintaining appropriate blood pressure through production of nitric oxide. The 894TT genotype of 894G>T (Glu298Asp, rs1799983), a polymorphic variant of eNOS, has been associated with several vascular diseases. On the basis of this strong relationship, we monitored daily 585 critically ill adult patients according to their degree of CVS dysfunction and investigated their disease prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
2
0
1
Order By: Relevance
“…Aspartate at position 298 was shown to be subjected to selective proteolytic cleavage in endothelial cells and vascular tissues that may be responsible for the T allele being a risk factor for vascular disease 24 . Indeed, Fraga et al 45 . found that the degree of cardiovascular dysfunction was higher in 894TT patients with sepsis, indicating that the effect of this genotype is an independent factor of cardiovascular dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Aspartate at position 298 was shown to be subjected to selective proteolytic cleavage in endothelial cells and vascular tissues that may be responsible for the T allele being a risk factor for vascular disease 24 . Indeed, Fraga et al 45 . found that the degree of cardiovascular dysfunction was higher in 894TT patients with sepsis, indicating that the effect of this genotype is an independent factor of cardiovascular dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a meta-analysis was conducted by Yao et al in 2010, declaring that rs1799983 was associated with reduced breast cancer risk (Yao et al, 2010). Furthermore, rs1799983 was also said to be related to many other diseases such as recurrent miscarriage (Luo et al, 2013) and cardiovascular diseases (Fraga et al, 2013). Considering the important role of NOS3 gene in the cancers and vasculopathy, we suggested that as one of the promising SNP rs1799983 might be the key polymorphism of NOS3 gene influencing CRC risk which might be useful in the genetic target therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Καταγράφηκε στατιστικά σημαντική μέση καρδιοαγγειακή τιμή βαθμολόγησης στην ομάδα των ασθενών με τον 894TT γονότυπο, η οποία και παρέμεινε στατιστικά σημαντική ανεξαρτήτως της υποομάδας στην οποία ανήκαν οι εκάστοτε ασθενείς (Πίνακας 3). Ως εκ τούτου, ο 894TT γονότυπος σχετίζεται με αυξημένο βαθμό καρδιοαγγειακής δυσλειτουργίας σε βαρέως πάσχοντες ασθενείς [295].…”
unclassified